LEGAL LIABILITY FOR THE ISSUANCE OF ADMINISTRATIVELY DEFECTIVE LAND RIGHTS CERTIFICATES - I Putu Marcellio Surya Diyasaputra; I Gusti Agung Ika Lakemi Mahadewi; Ida I Dewa Ayu Dwiyanti (International Journal of Business, Law and Political Science, 2026)
Objective: This study aims to analyze the legal responsibility for the issuance of land rights certificates containing administrative defects and the legal protection provided to certificate holders who suffer losses due to such defects. Method: This research employs an empirical legal research method using statutory, factual, and conceptual approaches. The data were collected through interviews with competent informants in the land sector and supported by secondary data derived from legislation, books, journals, and other legal literature. Results: The results indicate that legal responsibility for the issuance of administratively defective land rights certificates is implemented through mechanisms of correction, revocation, or cancellation of certificates in accordance with the applicable laws and regulations, particularly Law Number 30 of 2014 concerning Government Administration, Government Regulation Number 24 of 1997 concerning Land Registration, and Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 21 of 2020. Legal protection for affected certificate holders is provided through preventive and repressive legal measures, including administrative remedies and judicial proceedings. Novelty: This study concludes that effective legal responsibility and legal protection are essential to ensuring legal certainty, justice, and orderly land administration in Indonesia.